Italian validation of the German Pelvic Floor Questionnaire for pregnant and postpartum women. (May 2020) - Palmieri, Stefania; Cola, Alice; Ceccherelli, Anna; Manodoro, Stefano; Frigerio, Matteo; Vergani, Patrizia
Abstract: Objective: The only available validated questionnaire for pelvic floor disorders in pregnant and postpartum women is in German. The aim of this study was to translate and validate the German Pelvic Floor Questionnaire for pregnant and postpartum women into Italian. Study design: The questionnaire was translated into Italian by standardized procedural steps. The final version of the questionnaire was submitted to women in the third trimester of pregnancy or within 6 weeks post partum. Construct validity was tested using the Wilcoxon test, and internal consistency was tested using Cronbachʼs alpha. Test–retest reliability was measured with Cohenʼs kappa and intraclass correlation coefficient. Results: Fifty women answered the questionnaire. Construct validity was demonstrated, as the questionnaire discriminated significantly between patients with and without symptoms for four domains of pelvic floor disorders. Internal consistency was satisfactory (0.62–0.93). Cohenʼs kappa values for test–retest reliability were between 0.46 (moderate agreement) and 1.00 (complete agreement). Intraclass correlation coefficients ranged between 0.93 and 0.96, indicating very satisfactory overall agreement for each functional domain. Conclusions: The Italian version of the German Pelvic Floor Questionnaire for pregnant and postpartum women is reliable, valid and consistent.